Domestic sources of European foreign policy : defence and enlargement - Serrano, Omar (AUP - Film Culture in Transition., 2013)
When it comes to formulating foreign and pan-European policies, the European Union faces myriad challenges. The Domestic Sources of European Foreign Policy is an incisive study of these difficulties and their origins. It pays particular attention to the ways internal EU debates are influenced by domestic politics and political actors who legitimize or constrain support for shared policies. Ultimately revealing whether a democratic deficit exists in EU foreign policy, this book will be required reading for scholars and policy makers interested in European affairs and international relations.